Barriers to implementation of domestic violence prevention policies and programs in northwestern Ethiopia: A qualitative implementation research. - Agumasie Semahegn; Kwasi Torpey; Adom Manu; Nega Assefa; Naana Akyiamaa Agyeman; Augustine Ankomah (PLOS Global Public Health)
Ethiopia is a signatory to various international conventions, regional charters, and protocols related to violence against women, yet many women suffer domestic violence. To date, very little is known about how these conventions and protocols are being implemented, and the barriers associated with their implementation. This study explored the barriers to implementation of domestic violence against women prevention policies and programs in northwestern Ethiopia. We conducted a qualitative study using in-depth interviews, key informant interviews, and focus group discussions among 43 participants. The study participants were purposively selected based on their key roles and positions in implementing policies and programs that aim to prevent domestic violence against women in the study area. The interviews and discussions were audio-recorded after obtaining consent from each study participant. Data were transcribed, coded, and thematically analyzed using NVivo 11 software. Implementation of domestic violence prevention policies and programs at the local level is fraught with many budgetary constraints, poor planning, non-adherence to planned activities, lack of political will and commitment in the local settings, competing priorities, poor program integration, and weak inter-sectoral collaboration. Therefore, future interventions that would sustain and synergize domestic violence prevention through the intersectoral collaboration of key actors, ensuring budgetary issues, improving local governors' will and commitment, and transforming deep-rooted inequitable gender -norms for successful domestic violence prevention policies and programs implementation.